Company Taxation in the European Union; Opodatkowanie przedsiebiorstw w krajach Unii Europejskiej - Dorota Wawrzyniak (Comparative Economic Research. Central and Eastern Europe, 2011)
This paper investigates different measures of corporate tax burden ranging from the most basic ones such as the statutory tax rate to the effective tax rates. Each of these measures has advantages and disadvantages and they may lead to different rankings of countries. One of the reasons lies the fact that they measure different things. The comparison of the statutory tax rates to the effective ones for the EU-27 during the period of 1998-2009 sometimes reveals very significant differences between these indicators. Taking this into consideration, the paper suggests that corporate tax burden analysis should not be limited to the most basic and readily available measure in the form of the statutory tax rate. Different measures are tailored to answer different research questions. Moreover, the article presents changes of company taxation for the EU-27 within 1998-2009. – – W artykule dokonano przegladu miar obciazėnia podatkowego przedsiebiorstw. Rozpoczynajac od wielkosći najprostszych, jak stopa nominalna, a konćzac na miarach efektywnych. Kazḋy ze wskazńikoẃ ma wady i zalety, a jego wykorzystanie mozė prowadzicd́o roźṅego uszeregowania panśtw ze wzgledu na poziom opodatkowania. Jedna z przyczyn jest fakt, izẇielkosći te mierza inne rzeczy. Poroẃnanie stoṕ nominalnych i efektywnych w krajach UE-27, w latach 1998-2009, wskazuje na istnienie niekiedy bardzo istotnych roźṅic pomiedzy analizowanymi wskazńikami. W zwiazku z tym artykuł sugeruje, izṅie nalezẏ ograniczacánaliz opodatkowania przedsiebiorstw, do najprostszego i najłatwiej dostepnego wskazńika w postaci ustawowej stopy podatkowej a rozszerzycj́e o miary efektywne. Wielkosći te, stanowiace lepszy instrument do poroẃnanḿiedzynarodowych, umozl̇iwiaja przeprowadzenie wszechstronnych badan\'.
Keywords: 330